Exosome-mediated transfer of circRNA CircNFIX enhances temozolomide resistance in glioma. (1st June 2020) - Ding, Chenyu; Yi, Xuehan; Wu, Xiyue; Bu, Xingyao; Wang, Desheng; Wu, Zanyi; Zhang, Gaoqi; Gu, Jianjun; Kang, Dezhi
Abstract: Development of chemotherapy resistance remains a major obstacle for glioma management. Exosome-mediated transfer of circular RNAs (circRNAs) are being found to have relevance to many human cancers, including glioma. The purpose of this study is to explore the effect and underlying mechanism of exosomal circRNA nuclear factor I X (CircNFIX) on temozolomide (TMZ) chemoresistance in glioma. Our results indicated that exosomal CircNFIX was up-regulated in the serum of TMZ-resistant patients and predicted poor prognosis. Exosomal CircNFIX from TMZ-resistant cells conferred TMZ resistance to recipient sensitive cells through the enhancement of cell migration and invasion and the repression of cell apoptosis under TMZ exposure. CircNFIX directly interacted with miR-132 by binding to miR-132. CircNFIX knockdown enhanced TMZ sensitivity in resistant glioma cells by up-regulating miR-132. Additionally, exosomal CircNFIX promoted tumor growth and its depletion enhanced TMZ sensitivity in glioma cells in vivo . Taken together, our study suggests that exosome-mediated transfer of CircNFIX enhances TMZ resistance in glioma at least partially through sponging miR-132, highlighting a potentially prognostic biomarker and therapeutic target for improving the clinical benefits of TMZ treatment in patients with glioma. Highlights: CircNFIX was transferred by packaging into exosomes. Exosomal CircNFIX conferred TMZ resistance to recipient sensitive cells in glioma. CircNFIX directly interacted with miR-132 through sequestration. Exosomal CircNFIX enhanced glioma cell resistance to TMZ through sponging miR-132. Exosomal CircNFIX might serve as a prognostic biomarker and therapeutic target in patients with glioma.